2010
DOI: 10.19173/irrodl.v11i2.820
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between academic discipline and dialogic behavior in open university course forums

Abstract: The objective of this study was to determine the relationship between disciplinary difference (exact and natural sciences versus humanities) and the dialogic behavior that occurred in Open University course forums. Dialogic behavior was measured in terms of students' and instructors' active participation in the forum (posting a message) as well as amounts and proportions of "teaching presence," "cognitive presence," and "social presence." We found that active participation in the science forums was much higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 41 publications
1
29
1
1
Order By: Relevance
“…In particular, preservice teachers' posts at this level were at the information exchange indicator where pre-service teachers shared literature, resources and personal narratives of their experiences related to the topic. Other researchers (Kanuka & Anderson, 1998;Garrison et al, 2001;Luebeck & Bice, 2005;Vaughan & Garrison, 2005;Redmond & Mander, 2006;Gorsky et al, 2010) working in a range of different contexts have found similar results. The following pre-service teacher post is an example of the types of exploration posts:…”
Section: Findings and Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In particular, preservice teachers' posts at this level were at the information exchange indicator where pre-service teachers shared literature, resources and personal narratives of their experiences related to the topic. Other researchers (Kanuka & Anderson, 1998;Garrison et al, 2001;Luebeck & Bice, 2005;Vaughan & Garrison, 2005;Redmond & Mander, 2006;Gorsky et al, 2010) working in a range of different contexts have found similar results. The following pre-service teacher post is an example of the types of exploration posts:…”
Section: Findings and Discussionmentioning
confidence: 62%
“…It would also provide the opportunity for reflective posts to be coded at the higher level in the inquiry process, specifically, the level of resolution. This may also overcome some of the concerns that many researchers (Kanuka & Anderson, 1998;Luebeck & Bice, 2005;Vaughan & Garrison, 2005;Redmond & Mander, 2006;Gorsky et al, 2010), including the authors of the original framework, have directed towards the final phase of the framework, in that learners rarely move to the higher cognitive levels of the resolution phase.…”
Section: How Might Reflection Be Positioned Within Cognitive Presence?mentioning
confidence: 97%
“…Studies that investigate disciplinary differences in integrating interaction have Najafi, H., Rolheiser, C., Håklev, S., & Harrison, L. (2017 considered either a single mode or multiple modes of interaction in online courses. To probe the level of cognitive, instructional, and social presence in discussion forums of sciences and humanities courses offered in an Open University, Gorsky, Caspi, Antonovsky, Blau, and Mansur (2010) compared 25 discussion forums from science courses with 25 forums from humanities courses. Regarding the three dimensions of presence as defined by the Community of Inquiry model, humanities instructors were more active in the social presence dimension while science instructors showed higher levels of cognitive presence.…”
Section: Variations In Teaching Approachesmentioning
confidence: 99%
“…Regarding the three dimensions of presence as defined by the Community of Inquiry model, humanities instructors were more active in the social presence dimension while science instructors showed higher levels of cognitive presence. Within the cognitive presence dimension, Gorsky et al (2010) reported that science instructors posted more exploration messages compared with a higher number of triggering event posts sent by humanities instructors. The effect of instructional presence on learner participation in online discussions, however, is debated in online learning literature.…”
Section: Variations In Teaching Approachesmentioning
confidence: 99%
“…In an Israeli context using quantitative content analysis techniques in 50 forums with almost 5000 students participating, Gorsky et al (2010) studied the presence of Garrison et al's three key elements and found that the presence of these elements was higher in science forums than in the humanities, but that the ratio of the three elements was constant between the subjects. Social presence was the most prevalent, more than the other two elements together.…”
Section: Literature Reviewmentioning
confidence: 99%